Marriage Fear in Woman Who are Fatherless Perspectives of Islamic Law and Family Psychology - Masruroh, Siti; Musfiroh, Mayadina Rohmi; Hudi, Hudi (CV. Publikasi Indonesia, 2025)
Many fatherless women experience anxiety about marriage, which causes many women to marry at a very mature age. Marital anxiety can arise due to difficult past experiences, repeated feelings of worry, and, worst of all, not trusting other people, especially those of the opposite sex. This can give rise to various conflicts both for yourself and when you have a partner later. Regarding commitment, uncertainty about the future, and repetition of bad relationship patterns are the beginnings of various problems that become a stronghold for self-defence. Many of them choose to live without having relationships with the opposite sex. This article aims to explore the anxiety of women who experience fatherlessness, both in terms of the factors that cause them to choose to live single longer and even choose not to marry. This seems very warning to others, especially from the perspective of Islamic Law and Family Psychology. In this article, it is intended that anxiety about marriage will be reduced a little, although not completely, but just a little bit of their approach will also think about how the world should continue. This research uses descriptive qualitative research methods with semi-structured interviews and unstructured observations focusing on the criteria for women aged 20-35 years and relying on journal articles, literature and online magazines as other supporting media. The results of this article can be concluded that the four subjects who had marriage anxiety had reasons including factors related to non-hormonal family background, past experiences, social expectations and environmental pressure, uncertainty about partners, emotional and mental readiness, and demographic factors that made them afraid of having a serious relationship. In this article, it is found that anxiety tends to appear as a form of wrong self-protection, apart from that, families, the environment, and academics and practitioners are expected to design more effective support programs, especially for couples who want to continue their relationship in a more serious direction, providing a comfortable and safe space.